2020
DOI: 10.1590/1809-4392201904361
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary taurine supplementation on the growth and blood physiological parameters of juvenile pirarucu

Abstract: For some fish species, dietary taurine supplementation has been proven necessary in feeds with considerable utilization of vegetable proteins to substitute fishmeal. Pirarucu, Arapaima gigas feeds mainly on taurine-rich animal items in nature, therefore this study aimed to evaluate the effect of dietary taurine supplementation (0, 0.5, 1, 1.5 and 3%) on the growth and blood physiological parameters of juvenile pirarucu. A commercial feed was utilized as the basal diet for the experimental diets. Three hundred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
0
2
Order By: Relevance
“…They also found that taurine supplementation causes a decrease in the level of glucose in the blood of white seabream Diplodus sargus. However, the results of Rodrigues et al (2020) are not agreeable with the results of the current study, as they reported that taurine supplementation did not affect the physiological parameters of the blood, including glucose level in the pirarucu Arapaima gigas. The high blood sugar level in T1 can be attributed to the production of glucose after exposure to salt stress, which contributes to stimulating the process of building glucose from non-sugar materials (glyconeogenesis in the liver), in addition to taking glucose from the body (Nelson & Cox, 2005).…”
Section: Serum Glucose Contentcontrasting
confidence: 99%
See 1 more Smart Citation
“…They also found that taurine supplementation causes a decrease in the level of glucose in the blood of white seabream Diplodus sargus. However, the results of Rodrigues et al (2020) are not agreeable with the results of the current study, as they reported that taurine supplementation did not affect the physiological parameters of the blood, including glucose level in the pirarucu Arapaima gigas. The high blood sugar level in T1 can be attributed to the production of glucose after exposure to salt stress, which contributes to stimulating the process of building glucose from non-sugar materials (glyconeogenesis in the liver), in addition to taking glucose from the body (Nelson & Cox, 2005).…”
Section: Serum Glucose Contentcontrasting
confidence: 99%
“…The results of the current study did not agree with Rodrigues et al (2020), who showed that taurine supplementation did not affect the level of total protein and other physiological parameters in the pirarucu A. gigas.…”
Section: Serum Total Protein Contentcontrasting
confidence: 99%